(untitled) (Transport systems and technologies, 2018)
The study is devoted to estimating the vessel’s time in port by a shipowner-carrier, for whom it is important to understand the duration of port time under cargo handling as it is а part of the total time of the voyage, which in turn allows both to plan the vessel’s further work and to estimate the voyage costs. The reasoning is based on the wordings of the relevant terms of the charter party, most of which are negotiable between the shipowner and the charterer in the process of concluding a deal for the carriage of cargo (voyage charter party). Time in port is considered as the time for the direct cargo handling and additional time in the port, the presence and duration of which is actually determined by the wordings of the charter party’s terms. The influence of such wordings on the time in port under cargo handling was determined; it was found that to assess the duration of the time in port it is important to determine the time (day of the week and time) of the vessel’s actual arrival to the port for cargo handling. The time in port is structured chronologically, depending on the wordings of the terms of the charter party. The need for further development of the mathematical apparatus for estimating the probability of a vessel arriving to the port at certain time intervals was underlined.